2005
DOI: 10.1063/1.2135873
|View full text |Cite
|
Sign up to set email alerts
|

Excellent uniaxial alignment of poly(9,9-dioctylfluorenyl-2,7-diyl) induced by photoaligned polyimide films

Abstract: Articles you may be interested inPhoto-aligned blend films of azobenzene-containing polyimides with and without side-chains for inducing inclined alignment of liquid crystal molecules Electrical doping of poly(9,9-dioctylfluorenyl-2,7-diyl) with tetrafluorotetracyanoquinodimethane by solution method J. Appl. Phys. 97, 103705 (2005); 10.1063/1.1895470Enhanced electroluminescence from light-emitting devices based on poly(9,9-dihexadecylfluorene-2,7-diyl) and polysilane blends

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…For LED A (PFO/ZnO) it showed an emission peaks at 455 nm, 470 nm, and extended peaks with a two features at 510 nm and 540nm, the first two blue peaks correspond to the PFO as discussed above [28]. The first green peak appeared at 510 nm, this peak has recently been studied by R. Mallavia et al and they have shown that upon electron injection the PF polymers electrochemically degraded leading to the formation of new species and cross-linking of the polymer chains [29].…”
mentioning
confidence: 61%
“…For LED A (PFO/ZnO) it showed an emission peaks at 455 nm, 470 nm, and extended peaks with a two features at 510 nm and 540nm, the first two blue peaks correspond to the PFO as discussed above [28]. The first green peak appeared at 510 nm, this peak has recently been studied by R. Mallavia et al and they have shown that upon electron injection the PF polymers electrochemically degraded leading to the formation of new species and cross-linking of the polymer chains [29].…”
mentioning
confidence: 61%
“…LED A (ZnO NRs/PFO) has an emission peaks at 455 nm, 470 nm and 510 nm. The first two blue peaks corresponds to the PFO and they are due to the excitonic emission and its vibronic progression from non-interacting single chains [11], and the third peak which extended from 510 nm to 610 nm has been attributed to various defects sources that is either point defects such as oxygen vacancies V O , zinc vacancies V Zn , or due to recombination of electrons with surface states in ZnO [12]. LED B (MEH PPV/ZnO) has an extended emission from 575 nm to 750 nm with a peak centered at 605 nm which corresponds to the MEH PPV due to the PPV backbone that arises from the relaxation of excited Π-electrons to the ground state [13].…”
Section: Resultsmentioning
confidence: 99%
“…The PFO peak was detected with maximum intensity centered at 456nm. Some authors, such as K. Sakamoto et al, attribute this peak to excitonic emission and its vibronic progression from non interacting single chains [26]. Another broad peak centered at 510nm was detected, which represents the DBE of the ZnO material.…”
Section: Electroluminescencementioning
confidence: 99%